2010
DOI: 10.1103/physrevb.81.220406
|View full text |Cite
|
Sign up to set email alerts
|

Field-induced spin reorientation and giant spin-lattice coupling inEuFe2As2

Abstract: We have studied a EuFe 2 As 2 single crystal by neutron diffraction under magnetic fields up to 3.5 T and temperatures down to 2 K. A field induced spin reorientation is observed in the presence of a magnetic field along both the a and c axes, respectively. Above critical field, the ground state antiferromagnetic configuration of Eu 2+ moments transforms into a ferromagnetic structure with moments along the applied field direction. The magnetic phase diagram for Eu magnetic sublattice in EuFe 2 As 2 is present… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
71
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 27 publications
(31 reference statements)
10
71
0
Order By: Relevance
“…7,8 Works on EuFe 2 As 2 single crystals revealed that the Fe and Eu spins form long-range AFM order below 190 and 19 K, respectively. 9 Furthermore, the application of an external magnetic field will induce a magnetic phase transition in EuFe 2 As 2 with the Eu moments changing from AFM to FM arrangement, 10 while the AFM SDW order of Fe is found to be robust and it persists in the investigated field range up to 3 T. 11 The superconductivity can be achieved by applying high pressure or doping on any site in EuFe 2 As 2 . [12][13][14][15][16][17][18][19][20][21] Given the fact that a large in-plane electronic anisotropy exists in the AFM phase, [22][23][24] it is significant to understand the relationship between magnetism and electrical property of iron pnictide system.…”
Section: Introductionmentioning
confidence: 98%
“…7,8 Works on EuFe 2 As 2 single crystals revealed that the Fe and Eu spins form long-range AFM order below 190 and 19 K, respectively. 9 Furthermore, the application of an external magnetic field will induce a magnetic phase transition in EuFe 2 As 2 with the Eu moments changing from AFM to FM arrangement, 10 while the AFM SDW order of Fe is found to be robust and it persists in the investigated field range up to 3 T. 11 The superconductivity can be achieved by applying high pressure or doping on any site in EuFe 2 As 2 . [12][13][14][15][16][17][18][19][20][21] Given the fact that a large in-plane electronic anisotropy exists in the AFM phase, [22][23][24] it is significant to understand the relationship between magnetism and electrical property of iron pnictide system.…”
Section: Introductionmentioning
confidence: 98%
“…EuFe 2 As 2 exhibits a spin density wave (SDW) transition in the Fe sublattice concomitant with a structural phase transition at 190 K. In addition, Eu 2+ moments order in an A-type antiferromagnetic (AFM) structure at 19 K (ferromagnetic layers ordered antiferromagnetically along the c axis) [19][20][21]. Superconductivity can be achieved in this system by substituting Eu with K or Na (Refs.…”
Section: Introductionmentioning
confidence: 99%
“…22). 24 In addition, neutron diffraction measurements 23 suggested a canted AFM (C-AFM) structure of the Eu 2+ moments in EuFe 2 As 2 at intermediate magnetic fields.…”
Section: Introductionmentioning
confidence: 99%